SHAPING CHILDREN'S PERSONALITIES FROM AN EARLY AGE THROUGH FAITH AND MORAL EDUCATION AT SEMARANG CITY KINDERGARTEN: Membentuk kepribadian Anak Sejak Dini Melalui Pendidikan Akidah dan Akhlak di TK Kota Semarang - Anisa Alfiani; Agus Khunaifi; Mursid (SOSIOEDUKASI, 2025)
In the modern era filled with the influence of less educational media, moral problems in early childhood are increasing. Many children exhibit behavior that deviates from Islamic values such as honesty, helpfulness, and politeness. Therefore, faith and moral education from childhood is very important to build children's character based on Islamic teachings. This study aims to examine the application of faith and moral learning in Husna Jaya Kindergarten, Semarang City and assess its influence on the formation of Islamic character in children. The method used is qualitative descriptive research with data collection techniques in the form of observation, interviews, and documentation studies. The results of the study revealed that learning faith and morals through daily routines, teacher examples, Islamic stories, and parental involvement were effective in fostering positive attitudes such as honesty, mutual help, forgiveness, and good use of language. With a fun and consistent approach, moral education has proven to be the main foundation in shaping Islamic personality from an early age.